2017
DOI: 10.1021/acsmedchemlett.7b00404
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of JTZ-951: A HIF Prolyl Hydroxylase Inhibitor for the Treatment of Renal Anemia

Abstract: Inhibition of hypoxia inducible factor prolyl hydroxylase (PHD) represents a promising strategy for the discovery of a next generation treatment for renal anemia. We identified several 5,6-fused ring systems as novel scaffolds of the PHD inhibitor on the basis of pharmacophore analysis. In particular, triazolopyridine derivatives showed potent PHD2 inhibitory activities. Examination of the predominance of the triazolopyridines in potency by electrostatic calculations suggested favorable π-π stacking interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
(38 reference statements)
0
39
0
Order By: Relevance
“…Th., colorless solid. Analytical data in accordance with literature . 1 H‐NMR (300 MHz, CDCl 3 ) δ = 6.86, 6.82 (s, 2H, Im 4,5 ), 4.08 (t, J = 6.8 Hz, 2H, N‐C H 2 CH 2 ‐COO), 2.61 (t, J = 6.8 Hz, 2H, N‐CH 2 C H 2 ‐COO), 2.37 (s, 3H, Me), 1.39 (s, 9H, C(CH 3 ) 3 ) ppm.…”
Section: Methodsmentioning
confidence: 54%
“…Th., colorless solid. Analytical data in accordance with literature . 1 H‐NMR (300 MHz, CDCl 3 ) δ = 6.86, 6.82 (s, 2H, Im 4,5 ), 4.08 (t, J = 6.8 Hz, 2H, N‐C H 2 CH 2 ‐COO), 2.61 (t, J = 6.8 Hz, 2H, N‐CH 2 C H 2 ‐COO), 2.37 (s, 3H, Me), 1.39 (s, 9H, C(CH 3 ) 3 ) ppm.…”
Section: Methodsmentioning
confidence: 54%
“…Blood samples for quantitation of plasma JTZ-951 and metabolite (R)-M2 were collected at 0 hour (predose) and at 0.25, 0.5, 1, 1. 5,2,3,4,6,8,12,16,24,36,48,72,96, and 120 hours postdose. Blood samples for quantitation of plasma and whole-blood 14 C radioactivity were collected at the time points shown above (except at 0.25 and 3 hours), with additional collections at 144 and 168 hours postdose.…”
Section: Pharmacokinetic Assessmentsmentioning
confidence: 99%
“…JTZ-951 (enarodustat; chemical name: 2-({[7-Hydroxy-5-(2-phenylethyl)- [1,2,4]triazolo [1,5-a]pyridin-8-yl]carbonyl}amino) acetic acid) is a newly identified, orally available HIF-PH inhibitor. 8 In human HEP3B cells, JTZ-951 increased HIF-1α and HIF-2α protein levels, EPO mRNA levels, and EPO production. Nonclinical in vivo studies with JTZ-951 showed increases in hemoglobin concentrations without vascular endothelial growth factor-related effects on retinal permeability or tumor growth.…”
mentioning
confidence: 96%
“…12 We hypothesized that HIF stabilizers might reverse the metabolism alterations in diabetic renal cortical tissue, considering that HIF, as an adaptive response to hypoxia, reduces metabolic flux in cells to repress oxygen consumption. Thus, utilizing transcriptome and metabolome analyses, we conducted a proof-of-concept study to comprehensively understand how enarodustat (JTZ-951), 13,14 an oral HIF stabilizer, affects renal metabolism alterations occurring in the early stages of DKD.…”
mentioning
confidence: 99%